"Tout un monde nouveau à enfanter": utopie créatrice et maternité monstrueuse chez Zola - Béreiziat-Lang, Stephanie (HeLix, 2025)
Often seen as texts glorifying maternity and renewing the role of the monstrous woman of Les Rougon-Macquart, the Quatre Évangiles link motherhood to a new version of excess. By having the fertile woman physically erased in the text, the notion of maternity is de-corporalised, becomes a factor of monstrous multiplication, and delivers in retrospect a poetology for the writing processes of the Rougon-Macquart-cycle.
Gesehen am 02.06.2025